PENGARUH PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM (STUDI KASUS PT INDOFOOD CBP SUKSES MAKMUR TBK PERIODE TAHUN 2014-2024) - Ramdhani, Muhamad Iqbal; Mahroji, Dwi; Basir, Abdul (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
This study aims to examine the level of profitability indicated by the ROA ratio affecting stock prices, whether the dividend policy of the DPR ratio affects stock prices, and whether both affect stock prices simultaneously. Reports of total assets, profit/loss, and changes in equity. The object of this study is the stock price of PT Indofood CBP Sukses Makmur Tbk during the period 2014–2024. The type of data used in this study is quantitative data with sources in the form of secondary data, which comes from the financial statements of PT Indofood CBP Sukses Makmur Tbk research data comes from financial reports that can be obtained through the official website of the Indonesia Stock Exchange (IDX). The SPSS Version 23 application was used to conduct this study. The results of the study indicate that profitability has a positive and significant effect on stock prices. Conversely, dividend policy has a negative and significant effect on stock prices. Simultaneous results show that profitability and dividend policy together do not affect stock prices.